Identification of mycobiota from Tunisian olives and determination of their mycotoxigenic profile - Hamdi, Mohamed (2018)
In the Mediterranean basin, a large number of olive varieties are produced and cultivated. In Tunisia, olive culture represents one of the most significant agricultural products that is produced annually. Storage under inadequate conditions poses serious problems concerning fungal contamination, with consequent defects and potential mycotoxin production in olives and olive oils. In this study, we aimed to identify and characterize a selected group of fungi previously isolated from olives from Tunisian groves. For this purpose, 28 fungi were selected for identification by a polyphasic approach consisting of morphological identification on Malt Extract Agar (MEA) and Czapek Yeast Autolysate (CYA); physiological identification by the Erlich test (for the genus Penicillium only); and molecular identification by sequencing of the ITS region of the rRNA gene. Mycotoxigenic ability of fungi was screened on Coconut Agar Medium (CAM). Methanolic extracts of those fungi showing fluorescence on CAM wereobtained from CYA cultures and analysed by HPLC. From morphological and molecular identification, eight species belonging to the genera Alternaria, Aspergillus, Fusarium, Penicillium, Pleospora and Tricothecium and were identified. Results showed several isolates were able to produce toxins on CAM, by showing green or orange fluorescence. HPLC analysis are being developed.